СOMPARATIVE MORPHOLOGICAL AND ANATOMICAL INVESTIGATION OF THE VEGETATIVE ORGANS OF FILIPENDULA VULGARIS MOENCH. AND FILIPENDULA ULMARIA (L.) MAXIM. FROM THE NORTHERN CAUCASUS REGION - F. K. Serebryanaya; I. V. Geonya; K. M. Alieva (Фармация и фармакология (Пятигорск))
Introduction. Study for raw sources of a phytogenesis to obtain biological active substances with expressed pharmacological activity, attracts undoubted interest for the development of modern pharmaceutics.Objective. To carry out a comparative morphological and anatomical research of two types of Filipendula species: Filipendula vulgaris Moench. and Filipendula ulmaria (L.) Maxim., which grows in the North Caucasus.Methods. Samples of fresh-gathered plants were gathered (June, 2014-2015) in various areas of the North Caucasus to carry out a comparative micromorphological research (Pyatigorsk, a southwest slope of the mountain Mashuk, the open site of a meadow, Lermontov, the southern slope of Beshtau, an open meadow, KBR, the gorge of Bezengi, the right bank of Cherek Bezengiysky River, an inundated meadow, KBR, Dzhylysu Natural Boundary, a subalpine meadow), and also herb samples of a herbarium fund of department of botany and a pharmacognosy of the Pyatigorsk medico-pharmaceutical institute were taken. Studying of features of a micromorphological structure of both vegetative, and generative bodies of two types was carried out by reference techniques of microscopic and histochemical researches. Photography of fragments of a micromorphological structure of bodies was carried out by means of BIOMED-2 microscope with a photo of Digital microscope camera DMC-300.Results and discussion. Comparative morphological and anatomical researches of two types of the Filipendula species were conducted: Filipendula vulgaris Moench. and Filipendula ulmaria (L.) Maxim., which in the North Caucasus. Signs of distinctions of micromorphological features which allow carrying out diagnostics of medicinal vegetable raw materials were revealed. Distinctive features are the anomocytic stomata, trichomes in the form of the lengthiest straight lines and arched monocelled hairs, a form of a stalk and a scape on a transverse section, existence of omission of a scape and stalk, quantity and an arrangement of conductive bunches in a stalk and a scape of a leaf. The conducted researches are a fragment complex the pharmacognostical and ecological and biological researches of perspective resource species of the North Caucasus flora.